Teaching Methods used by EFL Teachers Towards Student Interest and Achievement in Writing: A Case Study at SMA Negeri 10 Sidrap - Sitti Aisa; Buhari .; Putri wulan suci; Jusman Tang; Andi Asrifan; nurhikmah .; Sam Hermansyah (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
This article investigates whether or not the use of a teacher way of teaching can improve the ability of SMAN 10 SIDRAP students to write descriptive compositions, as well as students' interest in learning to write descriptive compositions by using a teacher teaching method in classes X IPA and XI IPS. The descriptive qualitative approach was used in this study. The total population was 155 pupils, and two classes and two English teachers were chosen as samples using the saturation sampling approach, class X IPA (15) and XI IPS (15). In this study, the descriptive-composition and questionnaire were used to gauge students' interest. From the result of data analysis, the researcher found that the mean score of students Class X IPA (78.00) and students Class XI IPS (77.46). This shows that the score was above of curriculum standard. The researcher concluded that teachers teaching method in teaching writing-improved the students’ ability to write descriptive composition at X IPA and XI IPS, and the students interest Class X IPA (84.76) and students Class XI (85.17) it was categorized in strongly interested. It show that, the students of SMAN 10 SIDRAP-interested to learn write descriptive composition toward teachers teaching method.